A Survey on Multilevel Rectifiers With Reduced Switch Count - Ailton Do Egito Dutra; Montie Alves Vitorino; Mauricio Beltrao De Rossiter Correa (IEEE Access, 2023)
This paper presents a literature survey of more than twenty years on AC/DC multilevel converters with reduced switch count, in which some power switches can be removed letting only diodes. This simplification reduces the number of gate drivers, cost and complexity of the system. In this work, the considered topologies are derived from the conventional multilevel configurations on literature: Neutral Point Clamped, Cascaded H-Bridge, Flying Capacitor, Modular Multilevel Converter and T-Type. This article is divided in five sections, each one with papers with topologies derived from the five multilevel configurations previously mentioned. In each section, there are up to a maximum of four subsections, considering the main focus of each paper and contribution: derived and hybrid topologies, control techniques, analysis and hardware and design. At the end of each section, a summary table concerning the referenced papers is shown containing comparison information among the presented references in terms of: number of components per phase of the studied converter, applied modulation technique, applied control technique, suggested application given by the authors, converter’s output power considered and the respective efficiency considering this point of operation. With this extensive bibliography work, this paper serves as a very good reference to researchers interested in the topic to initiate their work or to update their studies. Also, the applications suggested by the authors give a direction of which topologies fit best different applications.